Health Forums and Twitter for Dementia Research: Opportunities and Considerations. Issue 12 (7th September 2020) - Mehta, Nishila; Zhu, Lynn; Lam, Kenneth; Stall, Nathan M.; Savage, Rachel; Read, Stephanie H.; Wu, Wei; Pop, Paula; Faulkner, Colin; Bronskill, Susan E.; Rochon, Paula A.
Abstract : BACKGROUND/OBJECTIVES: Social media platforms are promising sources for large quantities of participant‐driven research data and circumvent some common challenges when conducting dementia research. This study provides a summary of key considerations and recommendations about using these platforms as research tools for dementia. DESIGN: Mixed methods. SETTING: Alzheimerʼs Societyʼs online Dementia Talking Point forum from inception to April 17, 2018, and Twitter in February and March 2018. PARTICIPANTS: All users of Dementia Talking Point who posted in subforums labeled " I have dementia" and " I care for a person with dementia, " and Twitter users whose posts contained the keywords "dementia, " "Alzheimer, " or "Alzheimerʼs." MEASUREMENTS: We quantified the average daily number of dementia‐related posts on each platform and number of words per post. Guided by a codebook, we conducted thematic content analysis of 5% of the 15, 513 posts collected from Dementia Talking Point, and 10% of the 25, 948 comprehensible posts from Twitter containing "dementia, " "Alzheimer, " or "Alzheimerʼs." We also summarized research‐relevant characteristics inherent to platforms and posts. RESULTS: On average, Dementia Talking Point provided less than two new daily dementia‐related posts with 213.5 to 241.5 words, compared with 7, 883 new daily Twitter posts with 14.5 words. Persons with dementia (PWDs) commonly shared dementia‐related concerns (75.7%), experiences (68.6%), and requests for, as well as offers of, information and support (44.3% and 38.6%, respectively). Caregivers commonly shared caregiving experience (67.0%) and requests for information and support (52.5%). Most common dementia‐related Twitter posts were derogatory use of the term dementia (14.5%), advocacy, fundraising, and awareness (11.6%), and research dissemination (8.0%). Recommendations about these platformsʼ unique technical and ethical considerations are outlined. CONCLUSIONS: Understanding the priorities of PWDs and their caregivers remains important to understand how clinicians can best support them. This study will help clinicians and researcher to better leverage online health forums and Twitter for such dementia‐related information.